Using passive and active acoustic methods for impact damage assessment of composite structures. (15th October 2019) - Saeedifar, Milad; Mansvelder, Jasmijn; Mohammadi, Reza; Zarouchas, Dimitrios
Abstract: This study aims to use the passive and active acoustic-based health monitoring methods for impact damage assessment of composite structures. To this aim, a Carbon Fiber Reinforced Polymer (CFRP) composite plate was fabricated and subjected to a simulated low-velocity impact by performing repeated quasi-static indentation tests where a loading-unloading-reloading test profile with 5 repetitions was adopted. Two Acoustic Emission (AE) broadband sensors and a network of eight piezoelectric (PZT) sensors were attached on the composite plate surface. AE (passive method) was employed during the loading and reloading phases of the indentation tests to online monitor the critical damage occurrence and also specify the damage type while scanning of the plate with Lamb waves (active method) was done to localize the damage when the structure was unloaded. Felicity Ratio (FR) index which was calculated based on the AE data could accurately detect that critical damage occurred during the 5th loading-unloading-reloading stage when the structural integrity dropped to 60% of its initial stage. Furthermore, Lamb wave signals of central frequency 150 kHz localized the impact damage with error of 0.89 cm (3.6% error respect to the shortest dimension of the scanned area).